HEART UK statement on the management of homozygous familial hypercholesterolaemia in the United Kingdom. (December 2016) - France, Michael; Rees, Alan; Datta, Dev; Thompson, Gilbert; Capps, Nigel; Ferns, Gordon; Ramaswami, Uma; Seed, Mary; Neely, Dermot; Cramb, Robert; Shoulders, Carol; Barbir, Mahmoud; et al.
Abstract: This consensus statement addresses the current three main modalities of treatment of homozygous familial hypercholesterolaemia (HoFH): pharmacotherapy, lipoprotein (Lp) apheresis and liver transplantation. HoFH may cause very premature atheromatous arterial disease and death, despite treatment with Lp apheresis combined with statin, ezetimibe and bile acid sequestrants. Two new classes of drug, effective in lowering cholesterol in HoFH, are now licensed in the United Kingdom. Lomitapide is restricted to use in HoFH but, may cause fatty liver and is very expensive. PCSK9 inhibitors are quite effective in receptor defective HoFH, are safe and are less expensive. Lower treatment targets for lipid lowering in HoFH, in line with those for the general FH population, have been proposed to improve cardiovascular outcomes. HEART UK presents a strategy combining Lp apheresis with pharmacological treatment to achieve these targets in the United Kingdom (UK). Improved provision of Lp apheresis by use of existing infrastructure for extracorporeal treatments such as renal dialysis is promoted. The clinical management of adults and children with HoFH including advice on pregnancy and contraception are addressed. A premise of the HEART UK strategy is that the risk of early use of drug treatments beyond their licensed age restriction may be balanced against risks of liver transplantation or ineffective treatment in severely affected patients. This may be of interest beyond the UK. Highlights: Homozygous familial hypercholesterolaemia (HoFH) may cause atheromatous arterial disease and death in childhood despite conventional treatment. Lomitapide and evolucomab, which are effective in lowering cholesterol in HoFH, are now licensed in the United Kingdom. Lower treatment targets for lipid lowering in HoFH have been proposed to improve cardiovascular outcomes. HEART UK presents a strategy combining Lp apheresis with pharmacological treatment to achieve these targets in the United Kingdom (UK). Improved provision of Lp apheresis is needed in the UK and many other parts of the world. Early use of drug treatments beyond their licensed age restriction may be balanced against risks of liver transplantation.